PEMANFAATAN MEDIA PUBLISITAS HUMAS UNIVERSITAS HASANUDDIN DALAM PENYEBARAN INFORMASI PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA 2021 - Cahaya, Cahaya; Majid, Abd; Muttaqin, Andi (UNIVERSITAS MUSLIM INDONESIA, 2022)
The type of information submitted by PPID is information requested by the public while the information submitted by Public Relations is information related to activities and programs and things related to the needs of Hasanuddin University students. Media publicity is a publication tool used in disseminating information. This study aims to determine the role of Public Relations in utilizing the media publicity they have in this case is the Website unhas.ac.id and Instagram account with username @hasanuddin_univ regarding MBKM program information. This study uses descriptive qualitative approach, descriptive qualitative technique is a research method that utilizes qualitative data and described descriptively. The results showed that public relations of Hasanuddin University used their publicity media in disseminating information about the MBKM program in 2021. And also the message packaging strategy carried out by Hasanuddin University Public Relations can be considered satisfactory, by following the development of existing technology.